Cooperation or competition: species interactions across environmental gradients 2 - Wright, Alexandra (Henry Stewart Talks, 2026)
Popcorn clouds, Microclimate, Nurse species, Stress gradient hypothesis, Neighbor competition vs. facilitation, Sensitivity niche, Impact niche